1997
DOI: 10.1002/ana.410420406
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal dominant dementia with widespread neurofibrillary tangles

Abstract: Several familial dementing conditions with atypical features have been characterized, but only rarely is the neuropathology dominated solely by neurofibrillary lesions. We present a Midwestern American pedigree spanning four generations in which 15 individuals were affected by early-onset dementia with long disease duration, with an autosomal dominant inheritance pattern, and with tau-rich neurofibrillary pathology found in the brain post mortem. The average age at presentation was 55 years with gradual onset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
161
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(172 citation statements)
references
References 58 publications
11
161
0
Order By: Relevance
“…Using this cell model the effects of wild type and R406W mutant tau on cell morphology were examined, and the effects of the R406W mutation on tau localization and interactions with the cytoskeleton and microtubules were evaluated further. Previous cell models in which R406W mutant tau was expressed (20,22,23) were unable to reproduce the increased tau phosphorylation that occurs in FTDP-17 brains with this mutation (30,31). However, in this study we show that in stably transfected cortical cells, mutant R406W tau is more highly phosphorylated than wild type tau, and therefore this cell model provides an appropriate system to examine the effects of this mutation on tau function.…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…Using this cell model the effects of wild type and R406W mutant tau on cell morphology were examined, and the effects of the R406W mutation on tau localization and interactions with the cytoskeleton and microtubules were evaluated further. Previous cell models in which R406W mutant tau was expressed (20,22,23) were unable to reproduce the increased tau phosphorylation that occurs in FTDP-17 brains with this mutation (30,31). However, in this study we show that in stably transfected cortical cells, mutant R406W tau is more highly phosphorylated than wild type tau, and therefore this cell model provides an appropriate system to examine the effects of this mutation on tau function.…”
mentioning
confidence: 60%
“…Our group has previously shown that osmotic stress of SH-SY5Y cells results in activation of an apoptotic cascade (46). Because the R406W tau mutation is reported to have a relatively mild phenotype in the families (30) and therefore under normal conditions may not be toxic to cells, the cells were subjected to osmotic stress to determine if R406W mutant tau-expressing CN1.4 cortical cells were more vulnerable compared with cells expressing wild type tau. The results clearly demonstrated that R406W mutant tau does in fact exert a toxic effect under stress conditions in our cortical cell model, because there was more caspase activation in cells expressing R406W mutant tau compared with cells expressing wild type tau.…”
Section: Cellular Localization Of Wild Type and Mutant R406wmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphologies of tau filaments observed in the various forms of FTDP-17T vary (Crowther and Goedert 2000). Some mutations, such as V337M and R406W, produce filaments that appear identical to the paired helical and straight filaments of Alzheimer disease (Spillantini et al 1996;Reed et al 1997;Hutton et al 1998;Poorkaj et al 1998). All six tau isoforms are affected by the mutations and are incorporated into the filaments, which give rise to a pattern of tau bands on SDS-PAGE identical to that seen in Alzheimer disease.…”
Section: Implications For Understanding Alzheimer Diseasementioning
confidence: 99%
“…Among them, R406W mutant tau showed significantly reduced phosphorylation in those experiments. However, both mutant tau and wildtype tau deposited in FTDP-17 brains are also hyperphosphorylated (18,19). It is important to resolve the discrepancy between the reduced phosphorylation of mutant tau in vitro and in cultured neurons and the high phosphorylation of mutant tau in pathological brains.…”
mentioning
confidence: 99%